End-of-life care in Malaysia: the need for a regulatory reform - Alias, Fadhlina; Kassim, Puteri Nemie (World Association for Medical Law (WAML), 2021)
End-life care is an aspect of health care in Malaysia that is progressing in terms of delivery of services. It does not appear to be supported by a comprehensive regulatory framework, which includes proper ethical guidelines to facilitate doctors in making and implementing end-of-life decisions and legal safeguards in relation thereto. In other common law countries, where end-of-life care has achieved advanced status, these components are integrated in their health care policies, legislation and ethical codes. This paper proposes recommendations towards a more inclusive scheme that would facilitate and guide doctors in the end-of-life decision-making process on one end, while providing the requisite legal protection and assurance for doctors in the discharge of such duties, on the other.